Reversible particle movements associated with unstacking and restacking of chloroplast membranes in vitro (The Rockefeller University Press, 1976)
Freeze-fracture and freeze-etch techniques have been employed to study the supramolecular structure of isolated spinach chloroplast membranes and to monitor structural changes associated with in vitro unstacking and restacking of these membranes. High-resolution particle size histograms prepared from the four fracture faces of normal chloroplast membranes reveal the presence of four distinct categories of intramembranous particles that are nonrandomly distributed between grana and stroma membranes. The large surface particles show a one to one relationship with the EF-face particles. Since the distribution of these particles between grana and stroma membranes coincides with the distribution of photosystem II (PS II) activity, it is argued that they could be structural equivalents of PS II complexes. An interpretative model depicting the structural relationship between all categories of particles is presented. Experimental unstacking of chloroplast membranes in low-salt medium for at least 45 min leads to a reorganization of the lamellae and to a concomitant intermixing of the different categories of membrane particles by means of translational movements in the plane of the membrane. In vitro restacking of such experimentally unstacked chloroplast membranes can be achieved by adding 2-20 mM MgCl2 or 100-200 mM NaCl to the membrane suspension. Membranes allowed to restack for at least 1 h at room temperature demonstrate a resegregation of the EF-face particles into the newly formed stacked membrane regions to yield a pattern and a size distribution nearly indistinguishable from the normally stacked controls. Restacking occurs in two steps: a rapid adhesion of adjoining stromal membrane surfaces with little particle movement, and a slower diffusion of additional large intramembranous particles into the stacked regions where they become trapped. Chlorophyll a:chlorophyll b ratios of membrane fraction obtained from normal, unstacked, and restacked membranes show that the particle movements are paralleled by movements of pigment molecules. The directed and reversible movements of membrane particles in isolated chloroplasts are compared with those reported for particles of plasma membranes.